PROPER NAMES TRANSLATION TECHNIQUES: https://doi.org/10.5281/zenodo.17271666 - Aleshina , O.I. (International scientific and practical conference, 2025)
Thisarticleexamines the issues of translatingpropernames. The authorprovidestwoclassifications of translation,describes in detail the specifics of eachtranslationtransformation.Eachindividualtranslationtransformation is illustrated with examples.